2018
DOI: 10.1371/journal.pcbi.1006131
|View full text |Cite
|
Sign up to set email alerts
|

The complex ecosystem in non small cell lung cancer invasion

Abstract: Many tumors are characterized by genetic instability, producing an assortment of genetic variants of tumor cells called subclones. These tumors and their surrounding environments form complex multi-cellular ecosystems, where subclones compete for resources and cooperate to perform multiple tasks, including cancer invasion. Our recent empirical studies revealed existence of such distinct phenotypes of cancer cells, leaders and followers, in lung cancer. These two cellular subclones exchange a complex array of e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Three key characteristics defining collective invasion are: (i) the preservation of the physical connections and cell–cell junctions to orchestrate collective movement; (ii) shared cytoskeletal dynamics, allowing groups of cells to proceed as a single unit and develop multicellular polarity; and (iii) interactions with other cells and the ECM along the migratory path [26,27,28]. Collective invasion is a fundamental property of many metastatic tumours in human cancers, particularly epithelial tumours [29,30] including pancreatic cancer [31], colon cancer [32], sebaceous cancer [33], melanoma [34], breast cancer [35,36,37], and lung cancer [38].…”
Section: Collective Invasion and Leader Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three key characteristics defining collective invasion are: (i) the preservation of the physical connections and cell–cell junctions to orchestrate collective movement; (ii) shared cytoskeletal dynamics, allowing groups of cells to proceed as a single unit and develop multicellular polarity; and (iii) interactions with other cells and the ECM along the migratory path [26,27,28]. Collective invasion is a fundamental property of many metastatic tumours in human cancers, particularly epithelial tumours [29,30] including pancreatic cancer [31], colon cancer [32], sebaceous cancer [33], melanoma [34], breast cancer [35,36,37], and lung cancer [38].…”
Section: Collective Invasion and Leader Cellsmentioning
confidence: 99%
“…Leader cells may also secrete immune effector molecules, influencing lymphocyte differentiation and polarizing local immune responses towards a suppressive phenotype [49]. Several studies have now demonstrated the importance of leader cells in the progression of epithelial-tumour types including breast, salivary, bladder, prostate, and lung cancers [36,38,49,50,51].…”
Section: Leader Cells and Progenitor-like Propertiesmentioning
confidence: 99%
“…Collective cell migration is a widespread phenomenon that drives much of embryonic development, wound healing, and tumor metastasis. In migrating collectives, there are typically leader cells that extend protrusions outward from the group to steer it (Haney et al, 2018; Khalil and de Rooij, 2019; Theveneau and Linker, 2017; Zhang et al, 2019). The functions of follower cells are less clear (Qin et al, 2021), especially in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, targeting invasive leader cells is an active area of research for developing anti-metastatic therapies. By understanding the molecular and cellular mechanisms underlying their invasive behavior, researchers aim to identify specific targets or pathways that can be therapeutically targeted to suppress tumor invasion and metastasis [ 103 , 104 ].…”
Section: The Metabolic Characteristics Of Cscsmentioning
confidence: 99%